Quantum Gravity and Its Implications for Cosmology - Farid Akhmedov; Gulnar Guliyeva; Rania Al-Baker (Journal of Tecnologia Quantica, 2025)
The background of this research focuses on the confluence of two major theories in physics, namely quantum mechanics and general relativity, which are very important in explaining gravity at the quantum scale and cosmology. The purpose of this study is to investigate the relationship between quantum gravity theory and its implications for cosmological phenomena, especially related to singularities and enormous models of the universe. The method used in this study is a comparative analysis of various existing theories of quantum gravity, including string theory and quantum loop gravity, as well as a literature review on the application of these theories in cosmology. The results show that although various theories have been developed, there is not yet a clear consensus on how to integrate quantum gravity into the broader cosmological model. The study also revealed a huge gap in the experiments that could confirm these theories, which slowed down our understanding of gravity at the quantum scale. The conclusion of this study is the importance of further research in experiments and theories to bring together the principles of quantum and general relativity, which is expected to lead to a new, more comprehensive model of cosmology and the universe.